Conducting polymer-metal oxide nanocomposite and their property towards energy storage: An overview - Gupta B.; Melvin A.A.; Revathi P.; Matthews T.; Dash S.; Tyagi A.K.; Prakash R. (My University, 2025)
Supercapacitors combine the unique properties of two type of energy storage devices i.e. battery and capacitor. Thus supercapacitor reveals higher energy and power densities than conventional batteries and capacitors. Energy storage in supercapacitor takes place by two distinct phenomena i.e. surface charging/discharging as well as redox reaction. For further improvement in the current state of art of supercapacitors, it is required to develop new and efficient conductive and electroactive materials to meet ever increasing energy storage demand. In this context, conducting polymer and transition metal oxides are the versatile classes of materials for further modification and several combinations. Moreover, the above materials in nano-scale dimensions exhibit unique properties or combinations of properties as needed for supercapacitor electrode application. Nanotechnology enabled material synthesis strategies, have pushed the specific energy storage capacity to ~ 1000 F/g. Supercapacitor design and construction are likely to reap these benefits. The present article attempts to bring forward specific advantages of nanoscale materials deposited by chemical means towards device applications. © 2014 Nova Science Publishers, Inc.